1983
DOI: 10.1159/000194554
|View full text |Cite
|
Sign up to set email alerts
|

Terbutaline Aerosol from a Metered Dose Inhaler with a 750-ml Spacer or as a Nebulized Solution

Abstract: The clinical effect of 1.0 mg terbutaline given as a pressurized aerosol with a 750-ml spacer was compared with that of 4.0 mg terbutaline given as a nebulized solution (Pari Inhalier Boy). No differences were found in the parameters measured – forced vital capacity, 1 s forced expiratory volume, forced mid-expiratory flow, and oscillatory resistance. The results indicate that the same clinical response to a given dose of a pressurized aerosol supplied with a 750-ml spacer has the same effect as a fourfold dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1987
1987
2003
2003

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…[53][54][55] Twenty three studies in adults showed clinical equivalence for inhaler devices and nebulisers for the main pulmonary outcomes (FEV 1 and PEFR) and no evidence of significant difference in other outcomes. [56][57][58][59][60][61][62][63][64][65][66][67][68][69] Figure 5 shows the standardised mean difference of FEV 1 between nebulisers and hand held inhaler devices for the delivery of β agonists in stable asthma. 54 57-60 62 63 65-67 69-71 Updated searching identified two further studies.…”
Section: Effectiveness Of Nebulisersmentioning
confidence: 99%
“…[53][54][55] Twenty three studies in adults showed clinical equivalence for inhaler devices and nebulisers for the main pulmonary outcomes (FEV 1 and PEFR) and no evidence of significant difference in other outcomes. [56][57][58][59][60][61][62][63][64][65][66][67][68][69] Figure 5 shows the standardised mean difference of FEV 1 between nebulisers and hand held inhaler devices for the delivery of β agonists in stable asthma. 54 57-60 62 63 65-67 69-71 Updated searching identified two further studies.…”
Section: Effectiveness Of Nebulisersmentioning
confidence: 99%